Atomically Dispersed Transition Metal-Nitrogen-Carbon Bifunctional Oxygen Electrocatalysts for Zinc-Air Batteries: Recent Advances and Future Perspectives - Dong, Fang; Wu, Mingjie; Chen, Zhangsen; Liu, Xianhu; Zhang, Gaixia; Qiao, Jinli; Sun, Shuhui (Nano-Micro Letters, 2021)
Rechargeable zinc-air batteries (ZABs) are currently receiving extensive attention because of their extremely high theoretical specific energy density, low manufacturing costs, and environmental friendliness. Exploring bifunctional catalysts with high activity and stability to overcome sluggish kinetics of oxygen reduction reaction and oxygen evolution reaction is critical for the development of rechargeable ZABs. Atomically dispersed metal-nitrogen-carbon (M-N-C) catalysts possessing prominent advantages of high metal atom utilization and electrocatalytic activity are promising candidates to promote oxygen electrocatalysis. In this work, general principles for designing atomically dispersed M-N-C are reviewed. Then, strategies aiming at enhancing the bifunctional catalytic activity and stability are presented. Finally, the challenges and perspectives of M-N-C bifunctional oxygen catalysts for ZABs are outlined. It is expected that this review will provide insights into the targeted optimization of atomically dispersed M-N-C catalysts in rechargeable ZABs. Highlights: 1 General principles for designing atomically dispersed metal-nitrogen-carbon (M–N-C) are briefly reviewed. 2 Strategies to enhance the bifunctional catalytic performance of atomically dispersed M–N-C are summarized. 3 Challenges and perspectives of M–N-C bifunctional oxygen catalysts for Rechargeable zinc-air batteries are discussed.